Physico-chemical assessment of a tropically matured secondary forest catchment in isolated Ayer Hitam forest reserve, Peninsular Malaysia - Nordin @ Ahmad Nordin, Siti Fatimah (2020)
The presence of isolated forest within rapidly developed areas plays a crucial role in providing water resources, regulating climate, filtering soil and water pollution and might as well acts as mitigator flood events. The main objective of this study is to assess the physico-chemical characteristics from Upper Rasau River Catchment (URRC) of matured secondary forest in Ayer Hitam Forest Reserve (AHFR) during baseflow and stormflow conditions. The physical properties of the streamflow could be categorized to the discharge (Q), turbidity, temperature, and total suspended sediments (TSS) while selected chemical properties particularly are dissolved oxygen (DO), pH, electrical conductivity (EC), salinity, and total dissolved solids (TDS). The 4.66 km2 experimental catchment is located within an isolated granite tropical forest, AHFR in the most developed metropolitan city in Malaysia, Klang Valley. Streamflow from the mature secondary forest catchment (>60 years post-logging) was monitored during baseflow (4-hourly basis) and stormflow conditions (30-minute intervals) from October 2016 until October 2017. River discharges were determined at the outlet of the URRC using average velocity area method, later will be used to developing rating curve. The river water quality was determined based on the National Water Quality Standard of Malaysia (NWQS). The results indicate that the baseflow discharges were ranging from 0.003 to 0.680 m3s-1, and from 0.010 to 1.090 m3s-1 for the stormevent discharges. Based on NWQS, only pH and suspended sediments fall under Class 3 during stormevents while other parameters were in Class I during both baseflow and stormflow conditions. The climate of AHFR is categorized as equatorial monsoon. The mean temperature is 26.49 °C while total annual rainfall is 2396.4 mm. The findings had providing baseline study which are useful to understand the streamflow behaviour towards physico-chemical properties of the matured secondary forest catchment during less period of rainfall and high period of rainfall.